Floristic diversity and conservation of the Regional Sanctuary of Piura Manglares San Pedro of Vice-Sechura - Charcape-Ravelo, Manuel (2005)
The present work was carried out with the aim to document the composition of the flowering plants of the Regional Sanctuary of Piura «Manglares San Pedro», of Vice-Sechura. Its importance resides in that it is the most southern mangrove forest in the Pacific of South America. The study was carried out from April of the 2000 until February of the 2004. For the realization of the present work periodic visits every two months to the place were undertaken, the plants were collected under the standard procedures. The samples were determined in the place and some were taken to the laboratory of Botany of the National University of Piura and the laboratory of Phanerogamic Botany of the National University of Trujillo for their definitive determination, then the samples were deposited in the Herbarium in formation of the National University of Piura. The mangrove forest primarily consists of trees and shrubs of Avicennia germinans (L.) L. (Verbenaceae) «mangle prieto». The present inventory reports 44 species of phanerogams belonging to 36 genera in 21 families from the Mangrove.